Penerapan Hak Imunitas Anggota Keluarga Perwakilan Diplomatik Berdasarkan Konvensi Wina 1961 - Kusman, Sarah Mutiah; Waryenti, Deli; Andika, Tri (Jurnal Ilmiah Kutei, 2023)
Immunity right of family members of diplomatic agent is required to help diplomats carry out their missions. However, they are frequently have engaged in activities that are contrary to the purpose of these rights. This study aims to examine the regulation of immunity right and privileges of family members of diplomat based on the 1961 Vienna Convention and its application based on cases of violations of its right. The normative legal method was used in this research, along with statutory, conceptual, and case approaches. The research found that the immunity right possessed by diplomat’s family is the right of immunity against exclusion and arrest, private residence and correspondence, the criminal jurisdiction of the receiving country, freedom of dues and taxes, freedom of customs, taxes and related levies items related to the scrapping mission. People who can enjoy these rights are spouses, any minor children or unmarried children who live with the members of the mission/diplomat. The application of this right and privileges can be enforced if it fulfills several conditions namely the person is part of the household and lives with a diplomat, respects the laws and regulations of the receiving state, and carrying out a diplomatic mission or function.